Target RNAs Strike Back on MicroRNAs - Fuchs Wightman, Federico; Giono, Luciana E.; Fededa, Juan Pablo; de la Mata, Manuel (Frontiers in Genetics, 2018)
MicroRNAs are extensively studied regulatory non-coding small RNAs that silence animal genes throughout most biological processes, typically doing so by binding to partially complementary sequences within target RNAs. A plethora of studies has described detailed mechanisms for microRNA biogenesis and function, as well as their temporal and spatial regulation during development. By inducing translational repression and/or degradation of their target RNAs, microRNAs can contribute to achieve highly specific cell- or tissue-specific gene expression, while their aberrant expression can lead to disease. Yet an unresolved aspect of microRNA biology is how such small RNA molecules are themselves cleared from the cell, especially under circumstances where fast microRNA turnover or specific degradation of individual microRNAs is required. In recent years, it was unexpectedly found that binding of specific target RNAs to microRNAs with extensive complementarity can reverse the outcome, triggering degradation of the bound microRNAs. This emerging pathway, named TDMD for Target RNA-Directed MicroRNA Degradation, leads to microRNA 3′-end tailing by the addition of A/U non-templated nucleotides, trimming or shortening from the 3′ end, and highly specific microRNA loss, providing a new layer of microRNA regulation. Originally described in flies and known to be triggered by viral RNAs, novel endogenous instances of TDMD have been uncovered and are now starting to be understood. Here, we review our current knowledge of this pathway and its potential role in the control and diversification of microRNA expression patterns.